Eksistensi Kabasano Sumangan pada Orang Muna di Kelurahan Kadia Kecamtan Kadia Kota Kendari - Nurtikawati Nurtikawati; Arfan Arfan; Rahmat Sewa Suraya (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
The Kabasano Sumanga tradition is a tradition used by the Muna community to pray for the souls of deceased family members to rest in peace and not disturb the living family. The aim of this study is to identify the process, functions, and factors that affect the change in the Kabasano Sumanga tradition among the Muna community. The method used in this study is qualitative, by collecting data through observation, interviews, documentation, and literature review, then analyzing the data. The results of the study show that the process of implementing the Kabasano Sumanga tradition begins with visiting the grave and haroa. The implementation of Kabasano Sumanga has personal, social, and religious functions. Factors that can affect changes in the Kabasano Sumanga tradition include population migration, economy, education, and understanding factors.